Sikap : Konsep dan Pengukuran - Susanta, Susanta (Jurnal Ilmu Administrasi dan Bisnis, 2006)
Consumer behaviour study try to look for some certain factors that forming consumer behaviour. By knowing these factors so that companies or marketer can control their consumer behaviour. It means marketer can stimulate the consumer in order to buy their product. Consequently, it need consumers attitudes analysis. Keywords: Consumer behaviour, attitudes consumers analysis.